2000
DOI: 10.1097/00002030-200007280-00001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the K103N resistance mutation in Ugandan women receiving nevirapine to prevent HIV-1 vertical transmission

Abstract: This preliminary study demonstrates that HIV-1 with the RT K103N mutation can be detected in some Ugandan women following a single dose of NVP. This suggests that non-nucleoside RT inhibitor resistance may be selected in some people by single dose NVP prophylaxis. Pharmacokinetic data suggested that a more prolonged exposure to NVP after dosing may favor selection of NVP-resistant HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(97 citation statements)
references
References 11 publications
3
92
0
2
Order By: Relevance
“…It is an indication of a high probability of the evolution of widespread resistance to protease and reverse transcriptase inhibitors in this population where subtype G and its recombinants are prevalent. A preliminary study had shown that the niverapine resistance mutations (K103N) were readily selected in Ugandan women who received a single dose prophylactic regimen at the onset of labor in the Phase I/II trial HIVNET 006 (Jackson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is an indication of a high probability of the evolution of widespread resistance to protease and reverse transcriptase inhibitors in this population where subtype G and its recombinants are prevalent. A preliminary study had shown that the niverapine resistance mutations (K103N) were readily selected in Ugandan women who received a single dose prophylactic regimen at the onset of labor in the Phase I/II trial HIVNET 006 (Jackson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Резистентность к ИП/р требует 5-8 мутаций (вы-сокий генетический барьер), поэтому, чтобы она сфор-мировалась, нужны одновременно и активная реплика-ция вируса, и высокая концентрация препарата. Только тогда у вируса с мутациями появляется эволюционное преимущество [15]. Однако ИП/р способны в достаточ-ной мере подавлять репликацию, чтобы воспользовать-ся своим преимуществом вирус не смог.…”
Section: влияние приверженности к терапии на развитие резистентностиunclassified
“…Subtype G strains are less susceptible in vitro to protease inhibitors (PIs), the rate of occurrence of nevirapine resistance-associated mutations after a single dose is significantly higher in women with HIV-1 subtype C than in women with subtype A or D 81,82 . Nevirapine prophylaxis used in the HIVNET 012 66 has been reported to result in selection of single point mutations strongly associated with high resistance to non-nucleoside reverse transcriptase inhibitors that were detectable in 19% of the mothers and 46% of the infants 83 . By contrast with HIVNET 012 ® , where intra partum and neonatal exposure to nevirapine or zidovudine was limited, the PETRA ® interventions led to ongoing maternal exposure to zidovudine plus lamivudine from 36 weeks gestation.…”
Section: Drug Resistance Viral Subtypes and Implications On Mtctmentioning
confidence: 99%